1992
DOI: 10.1159/000114105
|View full text |Cite
|
Sign up to set email alerts
|

Peak Density, Size and Regional Distribution of Ganglion Cells in the Retina of the Fur Seal <i>Callorhinus ursinus</i>

Abstract: The total number, size, topographic distribution and peak density of ganglion cells were studied in retinal wholemounts of the fur seal, Callorhinus ursinus. The cell distribution showed a distinct zone of high ganglion cell density. It was located in the temporal retinal quadrant, near the horizontal meridian, 10–12 mm (25–31°) from the optic disk. The peak cell density in this zone was 812–1332 cells/mm2 (mean 1053 cells/mm2), i.e. 125–205 cells/deg2 (mean 162 cells/deg2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 11 publications
8
44
0
Order By: Relevance
“…This estimate is comparable to the underwater visual acuity found in the behavioral investigation in Florida manatees Trichechus manatus latirostris (Bauer et al, 2003), which reported for one subject, in freshwater at 1-m distance, a minimum angle of resolution of 24 0 , and in saltwater, a best resolution of 21 0 (nb: a second subject was found to have a much poorer resolution of 56 0 ). The data indicate that the retinal resolution and visual acuity of the Florida manatee are markedly lower than that reported in whales and dolphins (9 0 -14 0 by Mass and Supin, 1995, 1999, 2002 and in pinnipeds (3 0 -8 0 by Mass and Supin, 1992, 2010Hanke et al, 2009). It is, however, slightly higher than that in the Amazon river dolphin (40 0 -45 0 by Mass and Supin, 1989).…”
Section: Ganglion Cell Density and Retinal Resolutionmentioning
confidence: 64%
See 1 more Smart Citation
“…This estimate is comparable to the underwater visual acuity found in the behavioral investigation in Florida manatees Trichechus manatus latirostris (Bauer et al, 2003), which reported for one subject, in freshwater at 1-m distance, a minimum angle of resolution of 24 0 , and in saltwater, a best resolution of 21 0 (nb: a second subject was found to have a much poorer resolution of 56 0 ). The data indicate that the retinal resolution and visual acuity of the Florida manatee are markedly lower than that reported in whales and dolphins (9 0 -14 0 by Mass and Supin, 1995, 1999, 2002 and in pinnipeds (3 0 -8 0 by Mass and Supin, 1992, 2010Hanke et al, 2009). It is, however, slightly higher than that in the Amazon river dolphin (40 0 -45 0 by Mass and Supin, 1989).…”
Section: Ganglion Cell Density and Retinal Resolutionmentioning
confidence: 64%
“…Many cetaceans, such as the common dolphin Delphinus delphis (Dral, 1983), bottlenose dolphin Tursiops truncatus (Dral, 1977;Mass and Supin, 1995), harbor porpoise Phocoena phocoena (Mass and Supin, 1986), Chinese river dolphin Lipotes vexillifer (Gao and Zhou, 1987), gray whale Eschrichtius gibbosus ), Dall's porpoise, and Minke whale Balaenoptera acutorostrata (Murayama et al, 1992(Murayama et al, , 1995, have two spots of high cell density, one in the nasal and the other in the temporal retinal quadrants. In pinnipeds, a high cell density area occurs as either a discrete spot (the northern fur seal, Mass and Supin, 1992; the Weddel seal, Welsch et al, 2001) or a streak (the walrus, Mass, 1992) or a combination of both (the sea otter Enhydra lutris, Mass and Supin, 2000; the harbor seal, Hanke et al, 2009; the Caspian Seal, Mass and Supin, 2010). All these patterns are different from that found in the manatee.…”
Section: Ganglion Cell Number and Distributionmentioning
confidence: 92%
“…Eye anatomy in pinnipeds, despite notable difference from cetaceans, has some common features reflecting adaptation to underwater vision (Fig. 3A,B) (Jamieson and Fisher, 1972;Mass, 1992;Mass and Supin, 1992. In particular, a characteristic feature is an almost spherical or slightly elliptical lens.…”
Section: Pinnipedsmentioning
confidence: 99%
“…7A-D). In the northern fur seal (Callorhinus ursinus), ganglion cells are mostly of 14 to 28 mm with the largest cells up to 50 mm (Mass and Supin, 1992); in the Steller sea lion (Eumetopias jubatus), the majority of cells are 10 to 25 mm with some cells are as large as 37 mm (Mass and Supin, 2005); in the harp seal (Pagophilus groenlandicus), typical cells are 20 to 30 mm with some cells were as large as 60 mm (Nagy and Ronald, 1970;Mass and Supin, 2003). Giant ganglion cells were noticed also in the retina of the harbor seal (Phoca vitulina) (Jamieson and Fisher, 1971).…”
Section: Pinnipedsmentioning
confidence: 99%
See 1 more Smart Citation